Removal of Nickel Ions Using A Biosorbent Bed (Laminaria saccharina) Algae - Kamar AL-Hamadani, Firas Hashim (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
The present study aims to remove nickel ions from solution of the simulated wastewater using (Laminaria saccharina) algae as a biosorbent material. Effects of experimental parameters such as temperature at (20 - 40) C⁰, pH at (3 - 7) at time (10 - 120) min on the removal efficiency were studied.Box-Wilson method was adopted to obtain a relationship between the above three experimental parameters and removal percentage of the nickel ions. The experimental data were fitted to second order polynomial model, and the optimum conditions for the removal process of nickel ions were obtained.The highest removal percentage of nickel ions obtained was 98.8 %, at best operating conditions (Temperature 35 C⁰, pH 5 and Time 10 min).